Advances in Low Cost Silver-Containing Thick Film Conductors. (1981) - Taylor, Barry E.; Felten, John J.; Horowitz, Samuel J.; Larry, John R.; Rosenberg, Richard M.
Abstract : Extensive use of thick film materials to manufacture resistor networks and hybrid integrated circuits has come about because of economic, processing and functional advantages over other technologies in the high volume production of miniaturized circuits. Inherent in the adoption of thick film technology for increasingly diverse applications has been the ability of thick film material suppliers to provide progressive performance improvements at lower cost concurrent with circuit manufacturer's needs. Since the first major commercial thick film adoption in the early sixties, when IBM adopted platinum gold conductors and palladium silver resistors in their 360 computers, rapid technological advances over the last decade have produced an increasing variety of hybrid circuits and networks. The wide adoption of thick film technology in all segments of the electronic industry has placed increasing demands on performance and processing latitude. This paper outlines the development of low cost silver-bearing conductors and describes the evolution of technology improvements to present day systems. The initial segment reviews the deficiencies of early Pd/Ag conductors, particularly solder leach resistance and degradation of soldered adhesion following high temperature storage, and focuses on the first Pd/Ag system which overcame these problems. Extension of this technology and subsequent improvements in both binders and vehicles to fulfill adhesion requirements to Al2 O3 substrates of varying chemistries and to meet demands for high speed printing are also described. The second segment gives an overview of the present understanding of thick film conductor composites from a mechanistic point of view. The various types of binder systems commonly employed in conductors are discussed in terms of how they effect a bond between the sintered metal and the substrate, and the advantages and disadvantages of each type. Metallurgical aspects of conductor/solder connections are considered and their effects on bond reliability following exposure to high temperature discussed. Rheological considerations of paste design are presented and related to printing performance. The final segment focuses on newer low cost, high performance material systems that have evolved over the past two years. The technologies of each system are reviewed in terms of metallurgy, binder and vehicle. Important functional properties are presented to illustrate cost/performance tradeoffs. Special emphasis is given to recently developed high Ag containing conductors which have outstanding soldered adhesion even after 1000 hours of storage at 150℃.